Risk factors of early onset type 2 diabetes mellitus in young adults ≤ 40 years old - Gunawan, Burhan; Soerachmad, Soesilowati; Hendrawan, Liana Dewi; Titus, Johana; Cendana, Vira (Universa Medicina, 2024)
BackgroundThe global prevalence of type 2 diabetes mellitus (T2DM) in adolescents and young adults is dramatically increasing. The aim of this study was to explore numerous risk factors for the occurrence of Pre-DM or T2DM in subjects aged ≤40 years. MethodsA cross-sectional study was conducted involving 100 subjects (50 subjects in the Pre-DM/T2DM group and 50 subjects in the Non Pre-DM/T2DM group). Main inclusion criteria: age ≤40 years, registered in our Diabetes and Endocrine Clinic. Data extracted included demographic, lifestyle, anthropometric, psychosocial, and family history data. Statistical analysis by binary logistic regression model. Results were considered significant at p<0.05 ResultsThere were no differences in demographic variables between the two groups. Multivariate analysis showed that cigarette smoking [aOR 3.17 (95% CI: 1.11-11.28)], hypertension [aOR 2.48 (95% CI: 1.23-7.19)] obesity [aOR 5.11 (95% CI: 2.12-8.21)], history of excessive calorie intake [aOR 3.40 (95% CI: 1.54-5.55)], poor stress management [aOR 2.33 (95% CI: 1.04-3.88)], depression [aOR 5.17 (95% CI:1.63-8.26)], short sleep duration [aOR 2.72 (95% CI: 1.25-6.95)], physical inactivity [aOR 6.14 (95% CI: 1.41-9.22)], family history of T2DM [aOR 6.29 (95% CI: 2.61-9.27)], family history of hypertension [aOR 5.26 (95% CI: 2.18-8.91] were significant influential risk factors of Pre-DM/T2DM. ConclusionThe most influential risk factor for the occurrence of early onset T2DM among young adults was family history of T2DM. Screening of family members of T2DM patients may lead to early intervention and reduced risk of subsequent complications.